Freud and the rule of law: from Totem and taboo to psychoanalytic jurisprudence - Brunner, José (2016)
Can the reflection of legal scholars concerning the rule of law be enriched by the cultural conception of Freud about law? This article develops this question, based on how the rule of law was conceived in modernity, from a reading of the work of Hume and Rousseau, in order to show the potential compatibility that this conception had with the later work of Freud. Thus, Freud’s thinking about law is presented as a dialectical or paradoxical civilizatory force, restraining the passions even though they drive it, from a reading of his work Totem and Taboo. In this reconstruction, the genealogy of law is portrayed, from his story of the primal horde, and unconscious dynamics behind the law itself. Then the uses that various legal scholars have made of Freud in writing about the rule of law are analyzed, criticizing how they neglect the tragic sentiment of the Freudian cultural vision regarding law. Finally, the article states that the notions developed by Freud can serve critical legal thinking only if the law is seen as part of the culture, which leads to consider legal studies as a form of cultural studies.